KARAKTER ORANG MADURA, NASIONALISME, DAN GLOBALISASI - ardhie raditya (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2020)
This paper is an essential part for those who are interested in Madurese Studies, which have been mostly written from outsiders’ point of views, mainly Western researchers. This paper aims to produce a counter-discourse to the writings of outsiders who tend to position the Madurese as a violent and destructive ethnicity. By utilizing the method of ethnographic imagination, it is shown that the honourable character of the Madurese is unlike what has been imagined in various Western or Colonial literature. The Madurese have a vital contribution to the nationalism of anti-colonial for the development of Indonesian culture after the independence period. The spirit of Islamic values and culture respects human dignity as the locomotive of the development of the noble character of the Madurese. After the New Order regime, the true character of the Madurese begins to scatter. Intolerant Islamic groups in Madura tried to use the momentum of democracy in Indonesia to oppose all forms of globalization products and Chinese minority groups that were considerably not aligned with their political agenda. Their presence could potentially threaten not only the development of the noble character of the Madurese, but also the integrity of the Indonesian nation.